Heavy machinery operators : Necessary competencies to reduce construction accidents - Gurcharan Singh Bedi, Jasvin Kaur Bedi; Abdul Rahimi, Abdul Rahman; Din, Zia Ud (IOP Publishing Ltd, 2021)
The construction industry has been consistently performing poorly in safety resulting in substantial human and economic losses globally. The hazard related to heavy machinery operations can lead to injury or fatality of operators, workers, or visitors. Thus, safety training of heavy machinery operators (HMOs) is crucial to perform their tasks safely on construction projects. HMOs face various risks due to complex work environments at a job site such as the presence of other workers, material flow, equipment motion, and temporary structures that limit the space for heavy machinery. This research identifies the causes of accidents and competencies required to eliminate these accidents associated with heavy machinery operators. To achieve that, interview data with fifteen construction project managers are analyzed. This study's findings suggest that the causes of heavy machinery accidents include insufficient maintenance, negligence of operators, inadequate training, human factor, and site condition. Conversely, the competencies to mitigate heavy machinery accidents are knowledge of safety incentives and penalties from safety training, the ability to conduct safety briefing, inspect heavy machinery and site conditions, and communication skills. Industry practitioners and researchers can use these findings to enhance construction productivity by creating a safe working environment at construction sites.